PEMAHAMAN NORMA BERLALU LINTAS PADA SISWA SMAN 7DAN SMKN 5 BANJARMASIN - Azrianoor Azrianoor (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2014)
Azrianoor. 2014. Passed understanding Norma Cross In SMK Students of SMAN 7 and SMKN 5 Banjarmasin. Thesis, Program Study of Citizenship and Pancasila Education,Department of Social Science Education, Faculty of Teacher Training and Education Science, University of Lambung Mangkurat. Counselor (I) Zainul Akhyar, (II)Harpani Matnuh.In this study examines the Passed Cross In SMK Students of SMAN 7 and SMKN 5 Banjarmasin. The purpose of this study to determine the background of students' understanding of the requirements to be allowed to use motor vehicles, motor driving ordinance, penal sanctions for violations of traffic rules and the impact of violations of traffic rules on the road.The method used is a qualitative method of data capture techniques through observation , interviews, focus group discussions ( FGD ), and documentation of the data sources were selected purposively. Testing the validity of the data can improve through perseverance, triangulation, and using reference materials.The Results showed students' understanding of the requirements to be allowed to use motorized vehicles for knowledge of traffic laws still do not understand, the omission of a police presence, absence by the school, and the presence of omission by the parents. The procedure for motor drive system is the lack of understanding and knowledge of how to drive motorized traffic rules, patterns of behavior or attitude in driving a motorcycle, provide socialization and appeal to the public, held a routine patrol, raid gear motorcycle standards and prohibitions for junior high school students to use bicycles motors. Penal sanctions for violations of traffic rules by the bad behavior of motorists who often do, and exposed to legal sanctions traffic rules. The impact of traffic rules violation on the highway is not orderly traffic, and an increase in accidents involving students.Based on the results of research to realize a student who obey the law for orderly traffic, traffic cop Sat Banjarmasin So should conduct a more intensive dissemination of the laws of the Republic of Indonesia Number 22 of 2009 on traffic and highway transportation for students, should all the parties concerned work together to address the problems of traffic norms neighbors, and students are expected to provide instances neighbor traffic rules, especially students PPKn course in dealing with various problems faced by the students about traffic norms and regulations.Keywords: Elapsed Understanding Cross, Student.Keywords: Elapsed Understanding Cross, Student.